Experimental and numerical investigation of cross-shaped stub CFSTs under axial compression. Issue 23 (22nd December 2021) - Hassam, Muhammad; Guo, Lanhui; Wang, Yunhe
Abstract : The cross-shaped concrete-filled steel tube (CFST) is a new shape of column, which avoids convex corners and increases the interior area of the room. Cross-shaped CFSTs possess high bearing capacity, good seismic performance and efficient construction speed. In this study, cross-shaped stub CFSTs under axial loading were tested. The key parameter is the width/thickness ratio of the cross-section. Experiments revealed that local buckling could be delayed and section capacity enhanced by reducing the tube width/thickness ratio. Moreover, a finite-element model was established using the commercial program Abaqus to simulate the compressive performance of the specimens. The results were used to confirm the precision of the finite-element model. Further, a parametric study was completed to inspect the effects of the tube width/thickness ratio, concrete strength and steel yield strength on the mechanical properties of specimens. Relying on the constitutive theoretical model of restrained concrete, an equation is recommended to calculate the section capacity of cross-shaped CFSTs. Finally, the practical outcomes and the calculated outcomes obtained from different design codes (AISC, AIJ, EC4, CECS and GB) were compared. The comparison results revealed that all recommended design codes underrate the section capacity of cross-shaped CFSTs.